2016
DOI: 10.1007/s10551-015-3008-3
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Impact of Leaders’ Humility on Team Effectiveness: an Empirical Study

Abstract: We assess the perceived impact of leaders humility (both self and other-reported) on team effectiveness, and how this relationship is mediated by balanced processing of information. Ninetysix leaders (plus 307 subordinates, 96 supervisors, and 656 peers of those leaders) participate in the study. The findings suggest that humility in leaders (as reported by others/peers) is indirectly (i.e., through balanced processing) related to leaders' perceived impact on team effectiveness. The study also corroborates lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
96
1
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(110 citation statements)
references
References 80 publications
(96 reference statements)
3
96
1
10
Order By: Relevance
“…At least two empirical studies have suggested that humble leaders in organizations also experience positive outcomes, namely through enjoying greater perceptions of leader effectiveness and transformational qualities by their followers. First, Rego et al (2016) found that humble leaders were perceived as positively impacting their work team's effectiveness. Leader humility was assessed through a 360-degree instrument that included self-and other-reports of items taken from Dennis and Bocarnea (2005) and Park et al (2004) and of items generated by the authors.…”
Section: Self Outcomes: Learning and Performance Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…At least two empirical studies have suggested that humble leaders in organizations also experience positive outcomes, namely through enjoying greater perceptions of leader effectiveness and transformational qualities by their followers. First, Rego et al (2016) found that humble leaders were perceived as positively impacting their work team's effectiveness. Leader humility was assessed through a 360-degree instrument that included self-and other-reports of items taken from Dennis and Bocarnea (2005) and Park et al (2004) and of items generated by the authors.…”
Section: Self Outcomes: Learning and Performance Outcomesmentioning
confidence: 99%
“…This relationship seems likely, given the humble leader's preferences for inclusive, collaborative and flexible decision-making processes. Similarly, additional attention to the humble leader's openness to others' ideas (including contrary ideas and criticisms) (Rego et al 2016) and his/her capacity to consider exploitation and exploration strategies simultaneously (Ou et al 2015) could extend the implications of humility to the broader strategy literature examining CEOs' and other top executive members' individual preferences in decisionmaking.…”
Section: Studying Humility and Its Effects: Extending Theory And Pracmentioning
confidence: 99%
“…Using a hidden profile task provided the ability to capture actual information flow within a group rather than the intent to engage in behaviors thought to facilitate information flow. Use of a hidden profile task also provided an objective measure of performance, rather than perceived effectiveness, which has been the outcome variable used in several previous empirical studies examining the effect of leader humility on group performance (Owens & Hekman, ; Rego et al, ; Rego & Simpson, ).…”
Section: Studymentioning
confidence: 99%
“…Humility comprises four factors: (a) self‐awareness, (b) a willingness to learn/teachability, (c) an appreciation of others/high‐other‐focus, and (d) low self‐focus (Beauchesne, ; Ou et al, ; Owens, ; Owens, Rowatt, & Wilkins, ; Ruberton, Kruse, & Lyubomirsky, ; Tangney, ) and has become a popular topic of late, with leader humility being linked to a number of positive outcomes (Merryman, ; Prime & Salib, ). Perhaps of most interest to those focused on humility in an organizational context is that humble leaders have been shown to positively influence group performance and effectiveness (Collins, ; Ou, Waldman, & Peterson, ; Owens & Hekman, ; Rego & Simpson, ). But while humble leaders appear to produce positive results in the groups and teams they lead, it is not clear what factors determine when humble leaders are effective or how they influence work processes and outcomes (Owens & Hekman, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation